Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.5650/jos.ess21064
|View full text |Cite
|
Sign up to set email alerts
|

Clarification of the Complexation Behaviour of 2,6-di-<i>O</i>-Methylated <i>β</i>-Cyclodextrin and Vitamin E and Radical Scavenging Ability of the Complex in Aqueous Solution

Abstract: IntroductionCyclodextrin CD is a cyclic oligosaccharide that typically consists of six, seven or eight glucose residues linked by an α-1,4 glycosidic bond 1 3 . Because of the presence of a hydrophobic internal cavity, CDs form inclusion complexes with vitamin E α -tocopherol; Toc , a representative lipophilic anti-oxidant in nature 4 7 . Toc, which comprises a chromanol head and a phytyl tail, is known to interfere with one or more propagation steps of the lipid peroxidation process 8 11 , and its complexatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…As a result, 2,6-DMCD formed a water-soluble inclusion complex with Toc and effectively enhanced its solubility, whereas β -CD and γ -CD exhibited a tendency to form large aggregates consisting of inclusion complexes in aqueous media, and α -CD neither exhibited solubility enhancement nor the development of aggregation. 2D ROESY nuclear magnetic resonance analysis showed the direct interaction between the chromanol ring and the sugar of 2,6-DMCD 68) , whereas the complexation of γ -CD was confirmed by the enhancement of fluorescence and the disappearance of asymmetrical methylene and symmetrical methyl stretching vibration in Fourier transform infrared spectra 67) . These behaviors have been interpreted as follows and summarized in Table 1; first, owing to the narrow pore size, the α -CD-Toc inclusion complex was rarely formed, and neither solubility enhancement nor stable dispersion was formed.…”
Section: Vitamin E Complex With Various Cds In the Absence Of Organic...mentioning
confidence: 96%
See 1 more Smart Citation
“…As a result, 2,6-DMCD formed a water-soluble inclusion complex with Toc and effectively enhanced its solubility, whereas β -CD and γ -CD exhibited a tendency to form large aggregates consisting of inclusion complexes in aqueous media, and α -CD neither exhibited solubility enhancement nor the development of aggregation. 2D ROESY nuclear magnetic resonance analysis showed the direct interaction between the chromanol ring and the sugar of 2,6-DMCD 68) , whereas the complexation of γ -CD was confirmed by the enhancement of fluorescence and the disappearance of asymmetrical methylene and symmetrical methyl stretching vibration in Fourier transform infrared spectra 67) . These behaviors have been interpreted as follows and summarized in Table 1; first, owing to the narrow pore size, the α -CD-Toc inclusion complex was rarely formed, and neither solubility enhancement nor stable dispersion was formed.…”
Section: Vitamin E Complex With Various Cds In the Absence Of Organic...mentioning
confidence: 96%
“…Vitamin E (Tocopherol; Toc) is a representative lipophilic antioxidant, consisting of a chromanol head and a phytyl tail 65,66) . Recently, a comprehensive comparative study on CD-Toc complexation in aqueous systems has been reported 67,68) . Namely, the effects of various CDs such as α -CD, β -CD, γ -CD, 2,6-di-O-methylated β -cyclodextrin (2,6-DMCD) , and randomly-methylated β -cyclodextrin (RDMCD) on aqueous systems containing inclusion complexes with Toc and 2,2,5,7,8-pentamethyl-6-chromanol (PMC) were investigated (Fig.…”
Section: Vitamin E Complex With Various Cds In the Absence Of Organic...mentioning
confidence: 99%
“…4b, black bars) . Whereas water-insoluble VE-γcyclodextrin systems yield a large sustained effect 27) , the rapid scavenging abilities of small VE dispersions are similar to that of VE solubilized in methylated βcyclodextrin 28) . Meanwhile, the large dispersion (diameter 460 nm) exhibited a sustained effect; after an initially fast radical scavenging effect, the effect gradually increased and reached the level of the other systems (Fig.…”
Section: Radical Scavenging Ability Of Ve Dispersionmentioning
confidence: 97%
“…This measurement is usually performed on α ,α -diphenyl-β -picrylhydrazyl radicals, but this species is insufficiently soluble in water in the absence of sufficient co-solvent such as ethanol or solubilizer such as cyclodextrin 35) . Instead we evaluated the ability of the VE disper- Stabilizer-free Vitamin E Nanovehicle sions to scavenge 2,2'-azino-bis (3-ethylbenzothiazoline-6-sulfonate (ABTS) radicals, which are water-soluble species 27,28,36) and can be evaluated in our water system.…”
Section: Radical Scavenging Ability Of Ve Dispersionmentioning
confidence: 99%
See 1 more Smart Citation